Applications of Internet of Things in animal science - Saxena S.; Shrivastava S.; Kumar A.; Sharma A. (My University, 2025)
Traditional animal farming and management methods are labor intensive and driven by very slim margins. The alarming rate of human population growth has put the animal sector into tremendous pressure, and for satisfying the increasing human demands, newer approaches are required to increase livestock productivity. In the last decade, there has been a rapid growth of the Internet of Things (IoT), which has provided novel perspectives and opportunities for exploitation of the technology in the animal sector. With continually improving rural Internet connectivity, Internet of Animal Health Things (IoAHT) is now an emerging concept for smart livestock farms that has the potential to transform the entire animal health paradigm. The rapid expansion of IoT in the animal sector is useful in generating a massive amount of meaningful data, and the ethical use of the collected data can improve animal productivity, health, and welfare and develop a data-driven business model for precision livestock farming. © 2021 Elsevier Inc. All rights reserved.